High holding voltage segmentation stacking silicon-controlled-rectifier structure with field implant as body ties blocking layer. (2nd March 2016) - Yen, Shiang-Shiou; Cheng, Chun-Hu; Lan, Yu-Pin; Chiu, Yu-Chien; Fan, Chia-Chi; Hsu, Hsiao-Hsuan; Chang, Shao-Chin; Jiang, Zhe-Wei; Hung, Li-Yue; Tsai, Chi-Chung; Chang, Chun-Yen
Abstract: High electrostatic discharge (ESD) protection robustness and good transient-induced latchup immunity are two important issues for high voltage integrate circuit application. In this study, we report a high-voltage-n-type-field (HVNF) implantation to act as the body ties blocking layer in segmented topology silicon-controlled-rectifier (SCR) structure in 0.11 µm 32 V high voltage process. This body ties blocking layer eliminate the elevated triggered voltage in segmented technique. Using a large resistance as shunt resistor in resistor assisted triggered SCRs stacking structure, the double snapback phenomenon is eliminate. The series SCR could be decoupled a sufficient voltage drop to turned-on when a very low current flow through the shunt resistor. The holding voltage and the failure current of 22 V and 3.4 A are achieved in the best condition of segmented topology SCR stacking structure, respectively. It improves the latchup immunity at high voltage ICs application. On the other hand, the triggered voltage almost keep the same value which is identical to SCR single cell without using segmented topology.